Factors associated with uptake of cervical cancer screening among women aged 18-49 years attending care at a sub-county public health facility in Coastal Kenya (N = 315). - Dennis Mose (22683307) (2025)
Factors associated with uptake of cervical cancer screening among women aged 18-49 years attending care at a sub-county public health facility in Coastal Kenya (N = 315).